THE EFFECT OF REINFORCED POLYETHYLENE FIBER ON FLOWABLE RESIN COMPOSITE AS SPLINTING MATERIAL ON ATTACHEMENT OF Streptoccocus mutans : PENGARUH PENAMBAHAN POLYETHYLENE FIBER PADA RESIN KOMPOSIT FLOWABLE SEBAGAI BAHAN SPLINTING TERHADAP Streptococcus mutans - Ni Kadek Ari Astuti; Sumantri; Komang Sinta Kusumayanti (Interdental Jurnal Kedokteran Gigi (IJKG), 2022)
Introduction : Tooth mobility is one of the symptoms of periodontal disease which is characterized by loss of attachment and vertical bone damage. One method to overcome this is by splinting. The development of dental materials science has resulted in an innovative splinting technique using a thin band of material, easily bonded, consisting of a series of criss-crossed strands of thin polyethylene fibers. Fiber in the oral cavity will interact with saliva and microorganisms, especially Streptococcus mutans. Objective: The purpose of this study was to determine the effect of adding polyethylene fiber to flowable composite resin as a splinting material on the attachment of Streptococcus mutans. Materials and Methods: This research method was an experimental laboratory using a post-test only control group design. Samples in the form of blocks with a size of 5x4x2 mm were immersed in artificial saliva for 1 hour then soaked in liquid medium containing Streptococcus mutans and incubated for 2x24 hours, diluted to 100 or dilution of 10-2 then 0.1 mL of liquid medium put into TYC agar media in petridishes and incubated at 37oC for 48 hours anaerobically. Results and Discussion: Statistical tests showed that the addition of polyethylene fiber to the flow composite resin splinting material increased the attachment of Streptococcus mutans bacteria . The results of the Saphiro-Wilk test showed that the growth of Streptococcus mutans bacteria in each group was normally distributed (p>0.05). Lavene's test results obtained a statistical levene value of 0.695 with a significance value of 0.410 > 0.05, this proves that the data used is homogeneous. In the One Way Anova test, it can be seen that the sig value is 0.000 (p<0.05). From the results of the analysis with LSD shows there is a significant difference in treatment between variables. Conclusion: From the results of the study, there is an influence of the addition of polyethylene fiber to flowable composite resins as a splinting material on increasing the attachment of Streptococcus mutans.